2011
DOI: 10.4061/2011/202937
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of the First Three Steps of Gait Initiation in Patients with Parkinson's Disease with Freezing of Gait

Abstract: The purpose of this study was to investigate abnormalities of the first three steps of gait initiation in patients with Parkinson's disease (PD) with freezing of gait (FOG). Ten PD patients with FOG and 10 age-matched healthy controls performed self-generated gait initiation. The center of pressure (COP), heel contact positions, and spatiotemporal parameters were estimated from the vertical pressures on the surface of the force platform. The initial swing side of gait initiation was consistent among the trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
59
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 28 publications
11
59
1
Order By: Relevance
“…Furthermore, this finding was consistent with the finding in PD + FOG (Okada et al, 2011). Therefore, the decreased first COP peak displacement along the anteroposterior axis in PD + FOG likely reflects the abnormality of the postural phase of self-generated gait initiation in PD patients in general, but is not specifically related to FOG.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, this finding was consistent with the finding in PD + FOG (Okada et al, 2011). Therefore, the decreased first COP peak displacement along the anteroposterior axis in PD + FOG likely reflects the abnormality of the postural phase of self-generated gait initiation in PD patients in general, but is not specifically related to FOG.…”
Section: Discussionsupporting
confidence: 93%
“… Mean (SE of mean) . Asterisks indicate significant difference between PD patients and Healthy controls . Daggers indicate significant correlation between the parameter in PD + FOG and FOGQ item 5 . The data in PD + FOG were cited from the previous study (Okada et al, 2011) .…”
Section: Resultsmentioning
confidence: 99%
“…Abnormalities of gait initiation in people with PD have been previously described. Okada et al (2011) demonstrated that the duration of the initial step in patients with PD is significantly longer compared to healthy controls. Interestingly, no differences in duration were observed in the subsequent steps, indicating that certain motor pathways affected by PD are specific to the initiation of movement but not the rhythmic motor output that follows.…”
Section: Cycling Initiationmentioning
confidence: 98%
“…Abnormalities of gait initiation in people with PD has been previously described. Okada et al (2011) examined several parameters in the first three steps of gait following gait initiation in people with and without PD. Measurements included step length, step width, step time and step velocity.…”
Section: -23mentioning
confidence: 99%
See 1 more Smart Citation